2014
DOI: 10.1096/fj.13-249029
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide DNA methylation profiling identifies a folate‐sensitive region of differential methylation upstream of ZFP57 ‐imprinting regulator in humans

Abstract: Folate intake during pregnancy may affect the regulation of DNA methylation during fetal development. The genomic regions in the offspring that may be sensitive to folate exposure during in utero development have not been characterized. Using genome-scale profiling, we investigated DNA methylation in 2 immune cell types (CD4(+) and antigen-presenting cells) isolated from neonatal cord blood, selected on the basis of in utero folate exposure. High-folate (HF; n=11) and low-folate (LF; n=12) groups were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 31 publications
4
70
1
Order By: Relevance
“…While our analysis was restricted to a single purified cell type, we expect that any effects due to n-3 PUFA exposure during in utero development would be likely to propagate throughout the haematopoietic system and be present in other blood cell types, as we have reported before. 19 Despite this, it remains possible that other blood cell components, such as erythrocyte populations, may exhibit cell-type specific effect not observed in CD4s. Moreover, investigating the immune response capacity of CD4 C T-cells was beyond the scope of the present study and, therefore it remains possible that neonatal fish oil exposure may modify activation-induced effects on the neonatal DNA methylome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our analysis was restricted to a single purified cell type, we expect that any effects due to n-3 PUFA exposure during in utero development would be likely to propagate throughout the haematopoietic system and be present in other blood cell types, as we have reported before. 19 Despite this, it remains possible that other blood cell components, such as erythrocyte populations, may exhibit cell-type specific effect not observed in CD4s. Moreover, investigating the immune response capacity of CD4 C T-cells was beyond the scope of the present study and, therefore it remains possible that neonatal fish oil exposure may modify activation-induced effects on the neonatal DNA methylome.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 C T-cells were chosen as they play a key role in immune responses and have been shown to be susceptible to in utero perturbation from environmental exposures. 19,20 We hypothesized that maternal n-3 PUFA supplementation may modulate epigenetic programming of CD4…”
Section: Introductionmentioning
confidence: 99%
“…But the genomic regions in the offspring that may be sensitive to folate exposure during in utero development have not been characterized. Genome-wide DNA methylation profiling identifies a folate-sensitive region of differential methylation upstream of ZFP57-imprinting regulator in humans [292]. The underlying mechanisms of action also includeregulation of two microRNAs-let-7 and miR-34-by methylation [293].…”
Section: Autism -Paradigms Recent Research and Clinical Applicationsmentioning
confidence: 99%
“…Increased periconceptional folic acid consumption has been associated with increased methylation in infants at a differentially methylated region (DMR) of the IGF2 gene, although these associations have not been established consistently [56]. Additional studies have found that maternal folate levels in late pregnancy influence offspring methylation patterns in the imprinting control region of IGF2 [57] and also in the imprinting regulator ZFP57 [58]. Despite the timing of maternal folate measurements, these findings support the importance of nutritional status around conception, since many DMRs appear to have their methylation pattern established prior to gastrulation [59].…”
Section: Studies Investigating One-carbon Metabolites and Epigeneticsmentioning
confidence: 99%